The intersection of sex and race in the presence of deep-level attributes. Issue 5 (15th June 2015) - Kramer, Amit; Ben-Ner, Avner
Abstract : Purpose: – The purpose of this paper is to examine the mechanisms by which decisions about others are affected by the information known about them. The authors argue that the availability of information about deep-level attributes diminishes the role of surface-level attributes in how people make decisions about others. The authors posit that individuals will make discriminatory decisions based on surface-level attributes when only this information is available; but, as predicted by the integration-and-learning perspective, the availability of information about deep-level attributes will reduce surface-level attribute discrimination. Although discrimination will not disappear completely, it will shift its focal point toward a person's deep-level attributes. Design/methodology/approach: – Data were collected from subjects in two studies, with 52 subjects in Study 1 and 230 in Study 2. Paired-samples t -test and mixed effects GLS regression were used to test the hypotheses. Findings: – When presented with surface-level attributes of a target person, subjects demonstrated discriminatory behaviors based on race and sex. However, when subjects were presented with surface-level attributes along with deep-level attributes about a target person, subjects made decisions based on deep-level attribute similarities and disregarded surface-level information. Research limitations/implications: – The authors interpret the findings to mean that enhancing information about others shifts favoritism and discrimination based on surface-level attributes to "deeper" grounds. Originality/value: – This study demonstrates how multiple identities and values that individuals possess, and of which they become aware of in others, affect decision-making behavior toward others. It elucidates the mechanisms by which providing individuals with meaningful information about others can help them overcome, or at least reduce, surface-level discriminatory decision making.